Mericarp morphology of the tribe Selineae (Apiaceae, Apioideae) and its taxonomic implications in Korea - Lee, Changyoung; Kim, Jinki; Darshetkar, Ashwini M.; Choudhary, Ritesh Kumar; Park, Sang-Hong; Lee, Joongku; Choi, Sangho (Bangladesh Journal of Plant Taxonomy, 2018)
Mericarp morphology of 24 taxa belonging to nine genera of the tribe Selineae (Family: Apiaceae) in Korea was studied by Scanning Electron Microscopy. UPGMA and NMDS analyses were performed based on 12 morphological characters. The mericarp surface characters like mericarp shape, rib number and shape, surface pattern, surface appendages and mericarp symmetry proved useful in distinguishing the genera of the tribe Selineae.